Pengaruh Integerasi Filsafat Islam pada Manajemen Sekolah Negeri - Rizadiliyawati, Rizadiliyawati; Dahrani, Dahrani; Busra, Aminudin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This study explores the impact of integrating Islamic philosophy into the management of public schools. It examines how the principles of Islamic philosophy, such as justice, trust, patience, and sincerity, can influence leadership, human resource management, and curriculum development within educational institutions. By embedding Islamic values into school management, it is possible to foster a holistic educational environment that nurtures not only intellectual growth but also moral and spiritual development among students. The research highlights the potential benefits of incorporating these values into leadership practices, teacher-student relationships, and the overall school culture. However, it also discusses the challenges of applying Islamic principles in public schools with diverse cultural and religious backgrounds, emphasizing the need for an inclusive and balanced approach. Ultimately, the integration of Islamic philosophy in school management can contribute to the creation of a more effective and ethical educational system, producing well-rounded individuals who are not only academically competent but also possess strong moral character.Government in efforts to maintain harmony between religious communities